Grain size effect on the high-temperature hydrothermal stability of Cu/SAPO-34 catalysts for NH3-SCR. Issue 6 (December 2020) - Xu, Haidi; Lin, Chenlu; Lin, Qingjin; Feng, Xi; Zhang, Zhifeng; Wang, Yun; Chen, Yaoqiang
Graphical abstract: Highlights: The grain sizes affect the high-temperature hydrothermal (HTH) stability of Cu/SAPO-34. More CuO species in L-Cu/SAPO-34 turned into active Cu 2+ than those in S-Cu/SAPO-34. Re-distribution Cu 2+ prevent Si-O-Al bond opening during HTH treatment, keeping the structural integrity of Cu/SAPO-34. l-Cu/SAPO-34 experienced less damage of structure and kept NH3 -SCR activity better after HTH treatment. Abstract: The high-temperature hydrothermal (HTH) stability is always a key factor that affects the NH3 -SCR performance and limits the industrial applications of Cu/SAPO-34. Herein, two Cu/SAPO-34 catalysts with different grain sizes are HTH aged to investigate the role of the grain size of Cu/SAPO-34 in holding the structure stability of catalysts and the relationships between the grain size and deNOx performance over Cu/SAPO-34 during the HTH treatment. Characterization results illustrates that the relationship between the grain size and the stability of SAPO framework and the content of isolated Cu 2+ ions. During the HTH treatment, CuO species more easily transfer to isolated Cu 2+ species via migrating into the framework from the external surface of SAPO-34 for the larger-sized catalyst rather than the smaller-sized one. The re-distribution of Cu 2+ in the larger-sized catalyst prevents Si-O(H)-Al from H2 O attacking during HTH treatment. Therefore, the larger-sized Cu/SAPO-34 maintains stronger structural stability and higher deNOx activity than smaller-sized one after HTH treatment. This work provides a new strategy for design of high-temperature hydrothermal stabilized Cu/SAPO-34 for eliminating NOx emitted from diesel engines.